2014
DOI: 10.1097/mao.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Subjective Benefit With a Bone Conduction Implant Sound Processor in 44 Patients With Single-Sided Deafness

Abstract: The majority of the patients reported an overall improvement from using their BCI. However, the number of users decreases during a longer follow-up time and patients get less enthusiastic about the device after an extended period of use, especially in noisy situations. However, diminished satisfaction because of time-related reductions in processor function could not be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The APHAB scores of the first 29 patients were compared over time, and the mean scores for the EC, BN, and RV domains had increased—except for EC, significantly so, by 9 years postfitting compared with at 3 months and 1 year postfitting. Similar results were reported by Desmet et al, with diminished satisfaction over an extended period of use . Possible explanations for this increase in perceived disability might be adaptation to the benefits of the new hearing situation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The APHAB scores of the first 29 patients were compared over time, and the mean scores for the EC, BN, and RV domains had increased—except for EC, significantly so, by 9 years postfitting compared with at 3 months and 1 year postfitting. Similar results were reported by Desmet et al, with diminished satisfaction over an extended period of use . Possible explanations for this increase in perceived disability might be adaptation to the benefits of the new hearing situation.…”
Section: Discussionsupporting
confidence: 88%
“…Although the BAHI provides benefits, it also has limitations for patients with SSD, as suggested by the discontinuation of its use by 30% of the patients with the longest period of follow‐up (average of almost 10 years). Desmet et al report a discontinuation of 14% over a period of 50 months, attributing to about 3% per year . Considering the 10 years follow‐up in our study, the discontinuation seems on par with the study of Desmet et al The group of patients implanted after 2003 report a lower rate of discontinuation, namely 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the physical health score in GBI was worse for the reference device compared to the unaided condition. In the EC, BN, and RV categories, all patients improved with both the BCI and the reference device above the critical 22-point level ( Cox & Alexander, 1995 ), which is unusual in studies of bone conduction devices, where previous investigations have shown improvements of 16 to 34% of the patients ( Desmet et al, 2014 ; de Wolf et al, 2010 ).…”
Section: Discussionmentioning
confidence: 61%
“…The outcomes of the BBSS and the SSQ-B questionnaires used in this study were generally positive (89%). Only one patient (11 %) was dissatisfied, which corresponds to the findings of others (33).…”
Section: Discussionmentioning
confidence: 99%